Potential analysis of kompang's teaching in secondary school / Muhammad Hazim Azmi - Azmi, Muhammad Hazim (2023)
This research is about the Potential Analysis of Kompang. The aim of this study is to evaluate the existing kompang pedagogical methods in various institutions and to examine the development of kompang pedagogy periodically. There are two research questions. Why does it matter that teaching Kompang in a formal setting is crucial for teenagers in Malaysian secondary schools? and What is the problem that teenagers in Malaysian secondary schools face as a result of Kompang formal teaching in school?. This research engages a qualitative methodological approach using content analysis and observational techniques from secondary data.